The role of nervous system in the regulation of hemopoiesis - Ye. D. Goldberg; A. M. Dygai; Ye. G. Skourikhin (Бюллетень сибирской медицины, 2006)
Plastic change of hemopoietic tissue in experimental neurotic influences is under control of distant and local regulating mechanisms. Changes in compartments of erythroid and granulocitar hemopoiesis are due to specific spectrum of neuro-mediating systems. Receiving instructive information from the central nervous system is via αand β-adrenergic receptors on cell elements of hemopoiesing precursors. Manifestation of tropism of hemopoiesis to αor β-аdrenergic mechanisms is associated with nervous influence type. Existence of two different directions of plastic change of hemopoietic tissue in experimental neuroses : activation of blood system according to stressor type (conflict situation) and hemopoietic disturbances (deprivation of paradox sleep) is explained by the activity of regulation mechanisms.